Reduction of transients in switches using embedded machine learning - P. Suresh; S. George Fernandez; S. Vidyasagar; V. Kalyanasundaram; K. Vijayakumar; Vaidheeswaran Archana; Soham Chatterjee (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Non-linear loads can cause transients in electronic switches. They also result in a fluctuating output when the device is switched ON or OFF. These transients can harm not only the switches but also the devices that they are connected to, by passing excess currents or voltages to the devices. By applying machine learning, we can improve the gate drive voltages of the switches and thereby reduce switch transients. A feedback system is built that measures the output transients and then feeds it to a neural network algorithm that then gives a proper gate drive to the device. This will reduce transients and also improve performances of switch based devices like inverters and converters.